Concert: “La bande de Gluck: Accompanied Piano Music in Revolutionary Paris” - Beghin, Tom (Kouter, Ghent Club Falligan, 2024)
Program:C. W. Gluck, Iphigénie en Aulide, Wq. 40, arranged by J.-F. EdelmannJean-Frédéric Edelmann, Sonata in G Minor, Op. 6 No. 1D. Steibelt, Mélange d’airs et de chants, Op. 10C. W. Gluck, Echo et Narcisse, Wq. 47, arranged by J.-L. AdamJ.-L. Adam, Sonata in G Minor, Op. 7 No. 1Luca Montebugnoli, pianoLaura Andriani, violin
Abstract:Luca Montebugnoli (piano) and Laura Andriani (violin) explore links with Christoph Willibald Gluck’s operas in the accompanied piano music of Jean-Louis Adam, Jean-Frédéric Edelmann, and Daniel Steibelt. Playing a 1791 Pascal Taskin square piano, freshly restored by Pianos Maene (Ruiselede), they bring to life pre- and post-revolutionary repertoire from the Parisian salon, alternating original music for piano and violin with arrangements.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850